The Heliciculture in Colombia: Regulatory Reform and Productive Delay - Lopez Palechor, Leydy Evonne; Ruano Ibarra, Elizabeth del Socorro; Brisola, Marlon Vinicius (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Based on a historic-comparative approach it is analyzed the Colombian regulation of heliciculture in contrast to the official data on the exportable volume of Molluscs and the considerations of specialists in Colombia. The study takes into account the academic debate on the complementarity between the institutional and associative fields for the strengthening of agro-industrial sectors. A document review was conducted, which included the application of a structured questionnaire from the variables: legislation, productive structure and associativity. It is inferred that legal reforms did not significantly affect production and associativity. From this perspective the premise of effectiveness of the legal field in the creation of favorable conditions for strengthening rural activities with export potential is questioned.